POTENSI KERAMIK BONE CHINA SEBAGAI AKSESORIS FASHION ERA DIGITAL - Lusiana, Lusiana (Universitas Komputer Indonesia, 2017)
Translucent is a physical properties of Bone China. Bone ash materials gives Bone China Ceramics their unique properties, milky white color, translucent and light weight impression. So far, the use of Bone China ceramics have been focused on the character of a lighter weight impression than other ceramic materials. Transparency properties is limited used as lamp armature and hotel ware. This research is a qualitative descriptive study with theoretical analysis approach of ceramics, fashion accessories, consumer behavior theory by Solomon & Rabolt, and some data of phenomena as additional data to assess the chances of utilization a translucent ceramic material for fashion in the digital era. The results obtained are translucent ceramics has a great chance to be used as fashion accessories product with a mix of digital concept for middle class whose living in the digital era development.